The ordinary derivative of a function of one variable can be carried out
because everything else in the function is a constant and does not
affect the process of differentiation.
When there is more than one variable in a function it is often useful
to examine the variation of the function with respect to one of the
variables with all the other variables constrained to stay constant.
This is the purpose of a partial derivative.
For example, given the polynomial in variables x and y,
the partial derivative with respect to x is written
and the partial derivative with respect to y is written
The Partial Derivative
The ordinary derivative of a function of several variables with
respect to one of the independent variables, keeping all other
independent variables constant, is called the partial derivative
of the function.
Partial derivatives of f(x,y) with respect to x and y are denoted by
x
f
c
c
y
f
c
c
By definition
x
y x f y x x f
x
f
x
A
÷ A +
=
c
c
÷ A
) , ( ) , (
lim
0
y
y x f y y x f
y
f
y
A
÷ A +
=
c
c
÷ A
) , ( ) , (
lim
0
When these limits exist
Example:
2 3
3 2 ) , ( xy x y x f + =
2 2
3 6 y x
x
f
+ =
c
c
If
xy
y
f
6 =
c
c
Higher order partial derivatives
If f(x,y) has partial derivatives at each point (x.y) in a region, then and
are themselves fuctions of x and y, which may also have partial derivatives. These
second derivatives are denoted by
x f c c / y f c c /
2
2
x
f
x
f
x c
c
=

.

\

c
c
c
c
2
2
y
f
y
f
y c
c
=


.

\

c
c
c
c
2
2
z
f
z
f
z c
c
=

.

\

c
c
c
c
2
3
) , (
xy
e y x y x + = o find If
(a) (b) (c) (d)
(e) (f)
x c
co
y c
co

.

\

c
c
c
c
x x
o


.

\

c
c
c
c
y y
o
x yc c
c o
2
y xc c
c o
2
Example:
Solution:
(a)
x c
co
( )
2
3 xy
e y x
x
+
c
c
=
2 2
. 3
2
y e y x
xy
+ =
2
2 2
3
xy
e y y x + =
y c
co
( )
2
3 xy
e y x
y
+
c
c
=
xy e x
xy
2 .
2
3
+ =
2
. 2
3 xy
e xy x + =
(b)
0
2
2
2
2
2
2
=
c
c
+
c
c
+
c
c
z
U
y
U
x
U
( ) ( )
2 / 1
2 2 2
, ,
÷
+ + = z y x z y x U
suppose , show that
( ) ( ) 0 , 0 , 0 , , = z y x
We asume here that Then,
x
U
c
c
( ) x z y x 2 .
2
1 2 / 3
2 2 2
÷
+ + ÷ =
( )
2 / 3
2 2 2
÷
+ + ÷ = z y x x
2
2
x
U
c
c
( )  
2 / 3
2 2 2
÷
+ + ÷
c
c
= z y x x
x
( ) ( ) ( ) ( ) 1 . 2 .
2
3 2 / 3
2 2 2
2 / 5
2 2 2
÷ + + +
+ + ÷ ÷ =
÷ ÷
z y x x z y x x
( )
( )
( )
2 / 5
2 2 2
2 2 2
2 / 5
2 2 2
2
3
z y x
z y x
z y x
x
+ +
+ +
÷
+ +
=
( )
2 / 5
2 2 2
2 2 2
2
z y x
z y x
+ +
÷ ÷
=
2
2
y
U
c
c
( )
2 / 5
2 2 2
2 2 2
2
z y x
z x y
+ +
÷ ÷
=
2
2
z
U
c
c
( )
2 / 5
2 2 2
2 2 2
2
z y x
y x z
+ +
÷ ÷
=
2
2
2
2
2
2
z
U
y
U
x
U
c
c
+
c
c
+
c
c
Adding
( )
2 / 5
2 2 2
2 2 2
2
z y x
z y x
+ +
÷ ÷
=
( )
2 / 5
2 2 2
2 2 2
2
z y x
z x y
+ +
÷ ÷
+
( )
2 / 5
2 2 2
2 2 2
2
z y x
y x z
+ +
÷ ÷
+
( )
2 / 5
2 2 2
2 2 2 2 2 2 2 2 2
2 2 2
z y x
y x z z x y z y x
+ +
÷ ÷ + ÷ ÷ + ÷ ÷
=
( )
2 / 5
2 2 2
2 2 2 2 2 2
2 2 2 2 2 2
z y x
z z y y x x
+ +
÷ + ÷ + ÷
=
0 =